Starting Age Overshadowed: The Primacy of Differential Environmental and Family Support Effects on Second Language Attainment in an Instructional Context. (13th September 2018) - Pfenninger, Simone E.; Singleton, David
Abstract: Despite contrary research findings, many laypeople still claim that starting second language (L2) instruction early yields linguistic advantages. This assertion is again undermined by a 5‐year longitudinal study conducted in Switzerland testing the English language skills of 636 secondary‐school students who had all learned Standard German and French at primary school, but only half of whom had learned English from age 8, the remainder having started English 5 years later. The results suggest that age‐related attainment effects are overshadowed by other effects, yielding diverse outcomes according to individual differences and contextual effects mediating L2 outcomes. An earlier age of learning proved beneficial only for children raised as biliterate simultaneous bilinguals receiving substantial parental support, as opposed to monolinguals and nonbiliterate bilinguals (simultaneous or sequential). These issues require studies that explore what underlies age effects in L2 learning and investigate how learning contexts shape processes of L2 development.